(untitled) (London Journal of Research In Humanities and Social Sciences, 2025)
This article aims to describe the intricate history of the verb to be, focusing on its abundant inflection irregularities, from Old to Modern English. As any other research on historical linguistics, this article’s main goal is not only to point diachronic changes within the language, but also to explain how and why they happened, relying for such purpose on reputed theorists like Campbell (2013) and Bybee (2015), in addition to historical linguists whose works deal specifically with the development of the English language, such as Algeo (2010),Hogg &Fulk (2011), Ringe& Taylor (2014), among others. From a methodological point of view, this text displays each verbal tense on synoptic tables containing inflections from Old, Middle and Modern English, followed by several explanatory comments in order to clarify certain phonetic or morphologic phenomena. In short, one can say that the numerous irregularities found throughout the conjugation of the verb to be derive from the intermixing of two Old English verbs, bēonand wesan, which in turn were already irregular themselves.